2018
DOI: 10.3389/fimmu.2018.01965
|View full text |Cite
|
Sign up to set email alerts
|

Host Restriction Factors APOBEC3G/3F and Other Interferon-Related Gene Expressions Affect Early HIV-1 Infection in Northern Pig-Tailed Macaque (Macaca leonina)

Abstract: The northern pig-tailed macaques (NPMs) lack TRIM5α, an antiviral restriction factor, and instead have TRIM5-CypA. In our previous study, we demonstrated that HIV-1NL4−3 successfully infected NPMs and formed a long-term viral reservoir in vivo. However, the HIV-1-infected NPMs showed relatively high viremia in the first 6 weeks of infection, which declined thereafter suggesting that HIV-1 NL4−3 infection in these animals was only partly permissive. To optimize HIV-1 infection in NPMs therefore, we generated HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…The ethical reports highlight many of the related problems, including the stressful conditions during the transport of monkeys from their natural environment, and propose replacement variants, such as specially designed cells expressing human proteins that are implanted into smaller animals, such as rodents [76]. Despite this, valuable knowledge on many diseases that threaten humans has been gained through research with macaques, including studies of the immune system during HIV infection/AIDS progression [77,78], and in conjunction with HIV vaccine research [79], as well as through learning the details of the immune response in tuberculosis [80]. Another major problem faced in planning research on vertebrate animals is the inevitability of obtaining approval from an ethics committee to work with animals.…”
Section: Usefulness Of Animal Models and Their Limitationsmentioning
confidence: 99%
“…The ethical reports highlight many of the related problems, including the stressful conditions during the transport of monkeys from their natural environment, and propose replacement variants, such as specially designed cells expressing human proteins that are implanted into smaller animals, such as rodents [76]. Despite this, valuable knowledge on many diseases that threaten humans has been gained through research with macaques, including studies of the immune system during HIV infection/AIDS progression [77,78], and in conjunction with HIV vaccine research [79], as well as through learning the details of the immune response in tuberculosis [80]. Another major problem faced in planning research on vertebrate animals is the inevitability of obtaining approval from an ethics committee to work with animals.…”
Section: Usefulness Of Animal Models and Their Limitationsmentioning
confidence: 99%
“…However, only mild clinical manifestations and temporary cytokine increases have been observed in RMs ( Munster et al, 2020 ; Song et al, 2020 ). Previously, we confirmed that northern pig-tailed macaques ( Macaca leonina , NPMs) are a suitable animal model for acquired immune deficiency syndrome (AIDS) research ( Pang et al, 2018 ; Zhang et al, 2018 ). Different from RMs, NPMs can be infected with HIV-1 and viral reservoirs can form in vivo ( Pang et al, 2017 ).…”
mentioning
confidence: 72%
“…This is the first report to demonstrate the capability of CXCR4-tropic and CCR5-tropic HIV-1 derivative viruses to grow in rhesus macaques. Thus far, pig-tailed and cynomolgus macaques have been the only NHPs to perform in vivo infection studies on HIV-1/AIDS using viruses genetically recognizable as HIV-1 ( Igarashi et al, 2007 ; Hatziioannou et al, 2009 , 2014 ; Saito et al, 2011 , 2013 ; Thippeshappa et al, 2011 ; Otsuki et al, 2014 ; Peng et al, 2018 ). The rhesus macaque is by far the best suited NHP species for HIV-1 model studies from various points of views as described above.…”
Section: Discussionmentioning
confidence: 99%